2023
DOI: 10.1039/d2qi01919a
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrinic metal–organic frameworks as molybdenum adsorbents for the 99Mo/99mTc generator

Abstract: Two porphyrinic metal–organic frameworks (PCN-222 and PCN-224) were prepared and their potential as molybdenum adsorbents for the 99Mo/99mTc generator was explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…In particular, the Zr spectrum could be deconvoluted into two characteristic peaks of Zr 3d 5/2 at 182.2 eV and Zr 3d 3/2 at 184.6 eV. 66 Finally, the N 2 isotherm measurements revealed that the N 2 sorption capacity of the activated HCMUE-1 at P / P o = 0.95 was lower than the theoretically predicted data (Fig. S5†).…”
Section: Resultsmentioning
confidence: 78%
“…In particular, the Zr spectrum could be deconvoluted into two characteristic peaks of Zr 3d 5/2 at 182.2 eV and Zr 3d 3/2 at 184.6 eV. 66 Finally, the N 2 isotherm measurements revealed that the N 2 sorption capacity of the activated HCMUE-1 at P / P o = 0.95 was lower than the theoretically predicted data (Fig. S5†).…”
Section: Resultsmentioning
confidence: 78%
“…This was accompanied by the disappearance of the peak assigned to the N-H in-plane bending vibration of pyrrolic nitrogen (centered at ca. 963 cm −1 ) [34][35][36] that was only observed in the MOF-a material developed using the free-base H2TCPP. These data suggest that Cu 2+ remained in the porphyrin core even after the development of the MOF structure.…”
Section: Resultsmentioning
confidence: 95%
“…To further evidence the TCPP metalation, infrared spectra were also recorded (Figure S2b). The peak centered at 966 cm −1 assigned to the N-H in-plane bending vibration of pyrrolic nitrogen became undetectable after the treatment with Cu 2+ , suggesting an interaction between the -NH groups inside the porphyrin ring and copper ions [34][35][36]. In addition, a peak at ca.…”
Section: Resultsmentioning
confidence: 99%
“…The Mo 3d spectra was detected with well-defined splitting of 3d 5/2 and 3d 3/2 components having Δ BE = 3.1 eV, as shown in Figure e. The core level peaks observed at 231.8 and 234.9 eV are attributed to the Mo 3d 5/2 and Mo 3d 3/2 spin–orbit doublet states indicated to Mo 6+ , which proved that Mo-substituted the NiCo 2 O 4 successfully …”
Section: Resultsmentioning
confidence: 99%